(untitled) (Cambridge, Mass., 1990)
The Higgs Hunter's Guide is a definitive and comprehensive guide to the physics of Higgs bosons. In particular, it discusses the extended Higgs sectors required by those recent theoretical approaches that go beyond the Standard Model, including supersymmetry and superstring-inspired models.
Vật lý năng lượng cao
Keywords: Leptons (Vật lý hạt nhân),Leptons (Nuclear physics),Particles (nuclear physics),Các hạt (vật lý hạt nhân)